MUTATION PATTERN BASED ON TALENT MANAGEMENT: CASE STUDY AT FINANCIAL AND DEVELOPMENT SUPERVISORY BOARD INDONESIA - Boy Chandra Nababan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to build a mutation pattern policy based on Justice, Certainty, and Benefit. this policy is associated with talent management that has been implemented in Financial and Development Supervisory Board (BPKP). The method used in this research is a case study method based on phenomena that occur in BPKP. the result of this research is the formation of a mutation pattern policy, namely mutations based on organizational needs with the pattern Organization - Organization - Domicile and mutations based on employee needs. With this mutation pattern policy, employees are expected to improve their performance. But this research does not further examine the effect of this mutation policy on employee performance and also does not consider other factors such as age, gender of employee and Fund to apply this policy